Assessing public perception and willingness to pay for renewable energy in Pakistan through the theory of planned behavior - Ud Din, Shahab; Wimalasiri, Ruminda; Ehsan, Muhsan; Liang, Xue; Ning, Fulong; Guo, Dongdong; Manzoor, Zaira; Abu-Alam, Tamer; Abioui, Mohamed (Frontiers in Energy Research, 2023)
With the growing urbanization and world population, energy demand is also increasing. Significant portion of the world's energy comes from fossil fuels, and these sources of energy are declining rapidly at the current consumption rate. They are also growing environmental concerns as the use of fossil fuels increases greenhouse gas (GHG) emissions. In this regard, renewable energy (RE) shows promising solutions which are both sustainable and environmentally friendly. The developed countries and leading organizations are investing heavily in RE sector. However, the developing world has anxieties over social acceptability and people's willingness to pay for renewable energy. This study is conducted in Pakistan, to understand the public perception and willingness to pay. The theory of planned behavior (TPB) was utilized with background factors such as awareness, perceived advantages, perceived challenges, and moral obligations, to examine its influence on people's willingness to pay. In addition to this, the study also assessed the indirect effects of background factors (awareness, perceived advantages, and perceived challenges) on willingness to pay through attitude. Furthermore, the indirect relationship between background factors (awareness and moral obligation) and willingness to pay through subjective norms is also examined. A total of 512 samples were gathered from participants and were analyzed through partial least square structural equation modelling (PLS-SEM) and SPSS. The study findings are very interesting and backed up our hypotheses that the background factors (awareness, perceived advantages, and perceived challenges) are positively associated with attitude and have an indirect effect on willingness to pay through attitude. Similarly, variables such as awareness and moral obligation are negatively and positively associated with subjective norms, respectively. However, the variables (awareness and moral obligation) have no indirect relationship with willingness to pay through subjective norms. Additionally, the study revealed that the component of TPB (attitude and perceived behavior control) have a significantly positive effect on willingness to pay. The study also concluded that the participants having formal education and knowledge about climate change and renewable energy are inclined toward green energy and are willing to pay, and they are hardly influenced by others.